JUNIOR KYRGYZ CHILDREN’S PROSE PUBLISHED IN THE LAST 20 YEARS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article discusses in detail the features of the plot of children’s prose, methods of image formation and ideological and artistic skill.
Keywords: children’s prose, fairy tale, legend, story, book, child psychology, professional children’s literature.